1996
DOI: 10.1046/j.1365-2249.1996.d01-614.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids and reactive nitrogen intermediates collaborate in expression of the T cell mitogenesis-inhibitory activity of immunosuppressive macrophages induced in mycobacterial infection

Abstract: SUMMARYWe studied the role of phospholipids and nitric oxide in expression of the suppressor activity of splenic macrophages induced by Mycobacterium avium-intracellulare complex infection (MAICinduced macrophages) in mice against mitogenic response of concanavalin A (Con A)-stimulated splenocytes (SPC) as follows. First, phosphatidylserine (PS) and phosphatidylinositol were found to suppress Con A-induced mitogenesis of SPC via inhibition of IL-2 production and acquisition of IL-2 reactivity in Con A-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 12 publications
3
25
1
Order By: Relevance
“…We previously found that RNIs, free fatty acids (such as arachidonic acid), TGF-β, PGE 2 and phosphatidylserine inhibited T cell mitogenesis in a significant manner, thereby suggesting that these factors play roles as the suppressor mediators of MAC-MΦs [11][12][13]. Therefore, we next compared the susceptibilities of T cell and B cell mitogenesis to these suppressor mediators.…”
Section: Susceptibilities Of T Cell and B Cell Mitogenesis To The Dirmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found that RNIs, free fatty acids (such as arachidonic acid), TGF-β, PGE 2 and phosphatidylserine inhibited T cell mitogenesis in a significant manner, thereby suggesting that these factors play roles as the suppressor mediators of MAC-MΦs [11][12][13]. Therefore, we next compared the susceptibilities of T cell and B cell mitogenesis to these suppressor mediators.…”
Section: Susceptibilities Of T Cell and B Cell Mitogenesis To The Dirmentioning
confidence: 99%
“…In order to understand the role of RNIs, important mediators of suppressor M Φs [12,13,21,25,26], in the expression MAC-MΦ's suppressor activity against B cell mitogenesis, we compared the effects of L-NMMA on the MAC-MΦ-mediated suppression of the proliferative responses of SPCs to Con A and LPS stimulation. As indicated in Fig.…”
Section: Effects Of L-nmma a Nitric Oxide (No) Synthase Inhibitor Omentioning
confidence: 99%
See 1 more Smart Citation
“…BCG, Moureau strain, was obtained from the Ataulpho de Paiva Foundation, Rio de Janeiro, Brazil. The number of mycobacteria used in all assays was 8 ¥10 6 bacilli as described in the literature [9,10,12].…”
Section: Mycobacteriamentioning
confidence: 99%
“…Defective macrophage presentation would be responsible for the incapacity of lepromatous leprosy cells to respond to M. leprae [3]. In fact, the knowledge about inflammatory reactions in mycobacterial infections claims further advances [7][8][9][10]. Mycobacteria mediate mechanisms of escape within macrophages [8].…”
Section: Introductionmentioning
confidence: 99%